Impermeable anti-freezing alkali-activated geopolymer cementing material and preparation method thereof
By calcining and modifying marine mud with organic acids, and combining it with fly ash and desulfurized gypsum to prepare porous skeleton filling materials, and by using CO2 treatment and stepped steam curing processes, the problems of organic matter inhibition reaction and insufficient silicon activity in marine mud cementing materials were solved, thereby improving impermeability and frost resistance, and realizing the effective utilization of industrial solid waste and low-carbon production.
Patent Information
- Application Number
- CN202511543841.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-28
- Publication Date
- 2026-01-30
AI Technical Summary
Existing technologies have failed to effectively address the problems of organic matter inhibiting reaction and insufficient silicon activity in marine mud cementitious materials, resulting in insufficient impermeability and frost resistance, and have also failed to effectively utilize industrial solid wastes such as fly ash.
By calcining and modifying marine mud with organic acids, and combining it with fly ash and desulfurized gypsum to prepare a porous skeleton filling material, a gradient pore structure is designed. CO2 treatment and step-by-step steam curing processes are used to ensure that the alkali activation reaction is fully carried out, forming a dense three-dimensional silicon-aluminum network.
It significantly improves the impermeability and frost resistance of cementitious materials, reduces production costs, realizes the synergistic utilization of industrial solid waste, conforms to the concept of low-carbon development, and is suitable for harsh scenarios such as water conservancy and underground engineering.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of cementitious material preparation, and in particular to an impermeable and freeze-resistant alkali-activated geopolymer cementitious material and its preparation method. Background Technology
[0002] In the field of building materials, cementitious materials are the core foundation for ensuring the strength and durability of engineering structures. Traditional silicate cement requires high-temperature calcination during the production process, which not only consumes a large amount of non-renewable resources such as coal and limestone, but also emits huge amounts of carbon dioxide, exacerbating the global greenhouse effect and resource shortage problem.
[0003] Marine mud, as a widely existing natural sediment, is rich in silica and has low source cost, making it a potential raw material for alkali activation. However, the direct application of marine mud has obvious limitations: the organic matter in natural marine mud can hinder the diffusion and bonding of active ions, inhibiting the gelation reaction; the silica components are mostly in the form of inert silicates, which are not active enough to participate in polymerization; and the aluminum content of marine mud is low, which cannot meet the requirements of silicon-aluminum synergy for alkali activation reaction.
[0004] Regarding the aforementioned technologies, the inventors discovered that as the construction industry continues to demand higher performance from cementitious materials, some technologies attempt to incorporate solid wastes such as fly ash, marine mud, and bentonite into geopolymers. However, these are mostly simple mixtures without a systematic solution designed to address the characteristics of marine mud. They fail to eliminate organic interference and enhance silicon activity through modification, compensate for insufficient aluminum sources through component matching, or optimize the process to match the reaction characteristics of marine mud, resulting in insufficient durability properties such as impermeability and frost resistance in the materials. Summary of the Invention
[0005] In order to improve the shortcomings of existing geopolymer cementitious materials such as insufficient durability properties such as impermeability and freeze resistance, this application provides an impermeable and freeze-resistant alkali-activated geopolymer cementitious material and its preparation method.
[0006] In a first aspect, this application provides a permeability-resistant and freeze-resistant alkali-activated geopolymer cementitious material, employing the following technical solution: A permeability-resistant and freeze-resistant alkali-activated geopolymer cementitious material, comprising the following components by weight: 20-25 parts of modified marine mud; 40-50 parts of slag; 2-3 parts of compound alkali activator; The modified marine mud is marine mud particles modified with organic acids.
[0007] Based on the aforementioned technical solution, this application constructs a multi-component synergistic system according to the siliceous properties of marine mud and the core requirement of alkali-activated silicon-aluminum polymerization. After modification, marine mud can be transformed into a stable silicon source, replacing traditional high-cost siliceous raw materials and solving the problem of limited raw material sources. Through the complementary synergy between components, the alkali-activated reaction is ensured to proceed fully, forming a dense gel product. The three-dimensional silicon-aluminum network can reduce water penetration channels and improve impermeability. The tight structural bond can resist volume changes during freeze-thaw cycles and enhance freeze resistance.
[0008] Furthermore, the organic acid includes at least one of citric acid or phosphoric acid, and the proportion of the organic acid added is 1-5% of the marine mud.
[0009] Through the above technical solutions, this application addresses the two core problems of naturally occurring marine mud: "organic matter inhibiting the reaction" and "low silicon activity," and designs a two-step modification process of "calcination + organic acid activation." Calcination removes organic matter from the marine mud at high temperatures, preventing it from hindering the diffusion and bonding of active ions during subsequent alkali activation and preventing the formation of loose pores within the material. Crushing and sieving optimize the particle size distribution of the marine mud, increasing the specific surface area and providing more reaction sites for organic acid activation. Organic acids, through protonation, disrupt the crystal structure of silicates in the marine mud, dissolving some metal impurity ions and releasing silicon as active silicon ions, enhancing its ability to participate in polymerization reactions and solving the reaction lag problem caused by insufficient silicon activity when using marine mud directly.
[0010] Furthermore, it also includes 15-25 parts by weight of skeleton filler material, which is made using the following technical solution: First, fly ash and bentonite are mixed, heated and calcined, then allowed to cool to room temperature, and then crushed and collected to form porous skeleton particles. After mixing porous skeleton particles with desulfurized gypsum, the mixture is heated and subjected to a hydrothermal reaction. Sodium hydroxide solution is added, and the mixture is heated and pressurized. After the reaction is maintained at the same temperature and pressure, the mixture is allowed to cool to room temperature, washed, and dried to obtain the skeleton filling material.
[0011] Based on the above technical solution, this application designs a skeleton filling material with a gradient pore structure according to the requirements of impermeability and freeze-thaw resistance for the internal structure of the material. In the first step, fly ash and bentonite are mixed and calcined. Utilizing the silica-alumina components of fly ash and the layered structure of bentonite, porous skeleton particles with a certain porosity are formed at high temperature. These particles can provide structural support for the material and buffer the expansion stress generated by water freezing during freeze-thaw cycles through pores, thus preventing structural damage. In the second step, the porous skeleton particles undergo a hydrothermal reaction with desulfurized gypsum. The calcium element in the desulfurized gypsum reacts with the active silica-alumina components on the surface of the skeleton particles to generate hydration products, filling part of the pores to optimize density. Subsequent addition of sodium hydroxide solution and heating and pressurization can further promote the hydration reaction, enhance the bonding strength between the skeleton particles and the desulfurized gypsum, and prevent the skeleton from falling off or being unevenly dispersed during the molding process.
[0012] Furthermore, the mass ratio of the desulfurized gypsum to the porous skeleton particles in the porous skeleton particles is 1:(2.5-3.5).
[0013] Based on the above technical solution, this application determines the mass ratio of desulfurized gypsum to porous skeleton particles according to the balance requirement of "porosity-strength" of the skeleton filling material. If the proportion of desulfurized gypsum is too high, it will overfill the skeleton pores, resulting in too low porosity; if the proportion of desulfurized gypsum is too low, the skeleton pores cannot be fully filled, resulting in a loose structure, easy penetration of moisture into the material interior, poor impermeability, and insufficient skeleton support capacity, affecting the overall strength of the material. By adjusting the ratio of the two, the skeleton can form a moderately porous and dense structure, which retains the pore space to buffer freeze-thaw stress, and reduces the penetration path through desulfurized gypsum filling, thus meeting the dual requirements of impermeability and freeze-thaw resistance. This ratio design avoids skeleton performance defects caused by component imbalance, ensuring that the skeleton can play a structural support role and synergistically improve impermeability and freeze-thaw resistance; the ratio range has strong process adaptability, can accommodate the compositional fluctuations of different batches of raw materials, and reduce the difficulty of quality control in the production process; at the same time, a reasonable ratio can reduce raw material waste, control production costs while ensuring performance, and provide a guarantee for the stability and economy of industrial production.
[0014] Secondly, this application provides a method for preparing an impermeable and freeze-resistant alkali-activated geopolymer cementitious material, employing the following technical solution: A method for preparing an impermeable and freeze-resistant alkali-activated geopolymer cementitious material includes the following preparation steps: First, the modified marine mud and slag are mixed and stirred, then the skeleton filler material is added, stirred and mixed, and the mixture is collected. After taking the mixture and passing carbon dioxide gas through it, add the composite alkali activator, stir and mix, vibrate and mold it, steam cure it and then let it cure naturally for 14 days to prepare an impermeable and freeze-resistant alkali-activated geopolymer cementitious material.
[0015] Through the above technical solution, the process of this application achieves the goal of "uniform composition - dense structure - sufficient reaction", eliminating defects such as bubbles and agglomeration inside the material from the process level, and significantly improving impermeability (high density, few permeation channels) and freeze resistance (intact structure, strong freeze-thaw resistance); the process steps are clear, no special high-end equipment is required, and it is easy to scale up to industrial scale; compared with traditional processes, it can shorten the reaction cycle, improve production efficiency, and at the same time ensure the stability of material performance, taking into account both practicality and economy.
[0016] Furthermore, the parameters for introducing carbon dioxide gas are: pressure 0.1-0.2 MPa, rate 50-100 mL / min, and time 15-20 min.
[0017] Based on the reaction characteristics of CO2 with the system components and the environmental requirements of the alkali-activated reaction, this application determines the CO2 treatment parameters using the above-mentioned technical solution. These parameters ensure effective utilization of CO2, improve impermeability through calcium carbonate filling, and avoid its negative impact on the polymerization reaction, ensuring that the material's strength and freeze resistance are not compromised. The parameter range is mild, eliminating the need for high-pressure equipment and reducing production energy consumption and equipment investment. Simultaneously, it enhances the safety and economy of the process, enabling CO2 treatment to play a modifying role without increasing production burden, further optimizing the material's overall performance and production feasibility.
[0018] Furthermore, the steam curing is a stepped steam curing treatment, using the following technical solution: first steam curing at 40-45℃ for 2 hours, then steam curing at 60-65℃ for 4 hours, and finally steam curing at 80-85℃ for 2 hours.
[0019] Based on the above technical solution, this application designs a stepped steam curing process according to the temperature requirements of different stages of the alkali activation reaction. This curing process achieves "smooth start-up-efficient progress-full completion" of the alkali activation reaction, ensuring that the internal structure of the material is uniform and dense, without obvious defects. Compared with single-temperature curing, it can significantly improve impermeability and freeze resistance. At the same time, it avoids energy waste during the curing process, balancing effectiveness and energy economy, ensuring stable material performance and high production efficiency, and providing a reliable guarantee for quality control in industrial production. In summary, this application has the following beneficial effects: First, this application uses marine mud as the core raw material, combined with industrial solid waste such as fly ash and desulfurization gypsum. This not only solves the technical bottleneck of direct application of marine mud (by modifying it to eliminate organic interference and enhance silicon activity), but also achieves the synergistic utilization of industrial solid waste, significantly reducing dependence on traditional high-cost and scarce silicon-aluminum raw materials. Furthermore, compared to traditional Portland cement, the alkali-activated reaction consumes less energy, and the raw material side reduces pollution from industrial solid waste stockpiling. The entire process aligns with the low-carbon development concept, expanding the raw material channels for cementitious materials and promoting the transformation of resources from waste to treasure, thus achieving both environmental benefits and resource sustainability.
[0020] Secondly, this application utilizes multi-dimensional technological synergy to ensure the material's excellent impermeability and freeze-thaw resistance: In terms of formulation, the kaolin is precisely adjusted to adjust the silica-alumina ratio, ensuring a sufficient alkali-activated reaction and forming a dense three-dimensional silica-alumina network; the skeleton filling material is designed with a "moderate porosity + dense bonding" structure, which buffers freeze-thaw expansion stress and reduces permeation paths; in terms of process, CO2 treatment fills the micropores, and stepped steam curing optimizes the internal structure, avoiding "external strength and internal weakness" or stress cracking problems. Ultimately, this achieves a synergistic improvement in impermeability and freeze-thaw resistance, meeting the stringent requirements of water conservancy, underground engineering, and other demanding applications.
[0021] Third, this application balances process simplicity and cost control: the modification process and preparation flow do not require complex high-end equipment, resulting in a low operating threshold; CO2 treatment parameters and stepped curing temperatures reduce energy consumption and equipment investment, thus reducing the production burden; the raw materials, marine mud and industrial solid waste, are inexpensive, and the proportion design is compatible with batch fluctuations in raw materials, reducing the difficulty of quality control. The overall solution ensures high performance while considering the feasibility and economy of industrial production, avoiding the bottleneck of "high technology, high cost" in promotion. Detailed Implementation
[0022] The present application will be further described in detail below with reference to the embodiments.
[0023] The raw materials and instruments used in this embodiment are shown below, but are not limited thereto. Unless otherwise specified, the raw materials used are of analytical grade.
[0024] Preparation Example 1 Activated and modified marine mud particles 1 The marine mud was placed in a muffle furnace and calcined at 500℃ for 2 hours. After cooling, it was crushed and passed through a 200-mesh sieve. Oxalic acid with a mass fraction of 5-8% was added, and the liquid-solid ratio (mass ratio of water to marine mud particles) was controlled at 1:1.2. The mixture was stirred at 200 rpm for 1 hour at room temperature. After stirring, water was added and stirred, and then vacuum filtered. The filter cake was collected and dried to obtain modified marine mud 1.
[0025] Preparation Example 2 Activated and modified marine mud particles 2 The marine mud was placed in a muffle furnace and calcined at 550℃ for 2 hours. After cooling, it was crushed and passed through a 200-mesh sieve. Oxalic acid with a mass fraction of 6% was added, and the liquid-solid ratio (mass ratio of water to marine mud particles) was controlled at 1:1.3. The mixture was stirred at 250 rpm for 1 hour at room temperature (22°C). After stirring, water was added and stirred, and then vacuum filtered. The filter cake was collected and dried to obtain modified marine mud 2.
[0026] Preparation Example 3 Activated and modified marine mud particles 3 Take the marine mud and place it in a muffle furnace. Calcinate it at 500-600℃ for 2-3 hours. After cooling, crush it through a 200-mesh sieve. Add 8% oxalic acid by mass and control the liquid-solid ratio (water to marine mud particles mass ratio) to 1:1.5. Stir at 300 rpm for 2 hours at room temperature (25℃). After stirring, add water and stir again. Vacuum filter the mixture, collect the filter cake and dry it to obtain modified marine mud 3.
[0027] Preparation Example 4 Skeleton filling material 1 According to the mass ratio of fly ash to bentonite 1:1.5, fly ash and bentonite are first mixed, then heated and calcined. The calcination temperature is controlled at 800℃ and the holding time is 1.5h. After cooling to room temperature, the mixture is crushed and screened to collect 80-mesh porous skeleton particles. The porous framework particles were mixed with desulfurized gypsum at a mass ratio of 2.5:1 and then transferred to a hydrothermal reactor. The mixture was heated to 120°C and kept at that temperature for 2 hours. After adding 0.5 mol / L sodium hydroxide solution, the temperature was increased to 150°C and the pressure was increased to 0.2 MPa. The mixture was kept at that temperature and pressure for 1 hour. After cooling to room temperature, the mixture was washed and dried to obtain the framework filling material 1.
[0028] Preparation Example 5 Skeleton filling material 2 According to the mass ratio of fly ash to bentonite 1:2, fly ash and bentonite are first mixed, heated and calcined, the calcination temperature is controlled at 825℃ and the holding time is 2h, and then cooled to room temperature. The 115-mesh porous skeleton particles are then crushed, sieved and collected. The porous skeleton particles were mixed with desulfurized gypsum at a mass ratio of 3:1 and then transferred to a hydrothermal reactor. The mixture was heated to 130°C and kept at that temperature for 2 hours. After adding 0.5 mol / L sodium hydroxide solution, the temperature was increased to 160°C and the pressure was increased to 0.25 MPa. The mixture was kept at that temperature and pressure for 1 hour. After cooling to room temperature, the mixture was washed and dried to obtain the skeleton filling material 2.
[0029] Preparation Example 6 Skeleton filling material 3 According to the mass ratio of fly ash to bentonite 1:2.5, fly ash and bentonite are first mixed, then heated and calcined. The calcination temperature is controlled at 850℃ and the holding time is 2.5h. After cooling to room temperature, the mixture is crushed and screened to collect 150-mesh porous skeleton particles. The porous framework particles were mixed with desulfurized gypsum at a mass ratio of 3.5:1 and then transferred to a hydrothermal reactor. The mixture was heated to 140℃ and kept at that temperature for 3 hours. After adding 0.5 mol / L sodium hydroxide solution, the temperature was increased to 170℃ and the pressure was increased to 0.3 MPa. The mixture was kept at that temperature and pressure for 1.5 hours. After cooling to room temperature, the mixture was washed and dried to obtain the framework filling material 3.
[0030] Preparation Example 7 Compound Alkali Activator The composite alkali activator was prepared by mixing NaOH, water glass and Na2CO3 in a mass ratio of 1:3:1.
[0031] Example 1 A permeability-resistant and freeze-resistant alkali-activated geopolymer cementitious material, comprising the following substances: 20kg modified marine mud, 40kg slag, 5kg metakaolin, 2kg composite alkali activator; First, take modified marine mud, metakaolin and slag, mix and stir, and collect the mixture. After taking the mixture and introducing carbon dioxide gas with the following parameters: pressure 0.05 MPa, rate 50 mL / min, and time 20 min, a composite alkali activator is added. After stirring and mixing, the mixture is vibrated and molded. It is then steam-cured at 30℃ for 3 h, then steam-cured at 50℃ for 5 h, and finally steam-cured at 70℃ for 3 h, followed by natural curing for 14 days to prepare an impermeable and freeze-resistant alkali-activated geopolymer cementitious material.
[0032] Example 2 A permeability-resistant and freeze-resistant alkali-activated geopolymer cementitious material, comprising the following substances: 22kg modified marine mud, 45kg slag, 8kg metakaolin, 2kg composite alkali activator; First, take modified marine mud, metakaolin and slag, mix and stir, and collect the mixture. After taking the mixture and introducing carbon dioxide gas with the following parameters: pressure 0.08 MPa, rate 65 mL / min, and time 22 min, a composite alkali activator is added. After stirring and mixing, the mixture is vibrated and shaped. It is then steam-cured at 32℃ for 3 h, then at 52℃ for 5 h, and finally at 72℃ for 3 h, followed by natural curing for 14 days to obtain an impermeable and freeze-resistant alkali-activated geopolymer cementitious material.
[0033] Example 3 A permeability-resistant and freeze-resistant alkali-activated geopolymer cementitious material, comprising the following substances: 25kg modified marine mud, 50kg slag, 10kg metakaolin, 3kg composite alkali activator; First, take modified marine mud, metakaolin and slag, mix and stir, and collect the mixture. After taking the mixture and introducing carbon dioxide gas with the following parameters: pressure 0.1 MPa, rate 80 mL / min, and time 25 min, a composite alkali activator is added. After stirring and mixing, the mixture is vibrated and shaped. It is then steam-cured at 35℃ for 3 h, then steam-cured at 55℃ for 5 h, and finally steam-cured at 75℃ for 3 h, followed by natural curing for 14 days to prepare an impermeable and freeze-resistant alkali-activated geopolymer cementitious material.
[0034] Example 4 A permeability-resistant and freeze-resistant alkali-activated geopolymer cementitious material, comprising the following substances: 22kg modified marine mud, 45kg slag, 8kg metakaolin, 2kg composite alkali activator; First, take modified marine mud, metakaolin and slag, mix and stir, and collect the mixture. After taking the mixture and introducing carbon dioxide gas with the following parameters: pressure 0.08 MPa, rate 65 mL / min, and time 22 min, a composite alkali activator is added. After stirring and mixing, the mixture is vibrated and shaped. It is then steam-cured at 32℃ for 3 h, then at 52℃ for 5 h, and finally at 72℃ for 3 h, followed by natural curing for 14 days to obtain an impermeable and freeze-resistant alkali-activated geopolymer cementitious material.
[0035] Example 5 A permeability-resistant and freeze-resistant alkali-activated geopolymer cementitious material, comprising the following substances: 22kg modified marine mud, 3.45kg slag, 8kg metakaolin, 2kg composite alkali activator; First, take modified marine mud, metakaolin and slag, mix and stir, and collect the mixture. After taking the mixture and introducing carbon dioxide gas with the following parameters: pressure 0.08 MPa, rate 65 mL / min, and time 22 min, a composite alkali activator is added. After stirring and mixing, the mixture is vibrated and shaped. It is then steam-cured at 32℃ for 3 h, then at 52℃ for 5 h, and finally at 72℃ for 3 h, followed by natural curing for 14 days to obtain an impermeable and freeze-resistant alkali-activated geopolymer cementitious material.
[0036] Example 6 A permeability-resistant and freeze-resistant alkali-activated geopolymer cementitious material, comprising the following substances: 22kg modified marine mud, 1.45kg slag, 8kg metakaolin, 15kg skeleton filler material, 2kg composite alkali activator; First, take modified marine mud, metakaolin and slag, mix and stir, then add skeleton filler material 1 and stir and mix, and collect the mixture; After taking the mixture and introducing carbon dioxide gas with the following parameters: pressure 0.08 MPa, rate 65 mL / min, and time 22 min, a composite alkali activator is added. After stirring and mixing, the mixture is vibrated and shaped. It is then steam-cured at 32℃ for 3 h, then at 52℃ for 5 h, and finally at 72℃ for 3 h, followed by natural curing for 14 days to obtain an impermeable and freeze-resistant alkali-activated geopolymer cementitious material.
[0037] Example 7 A permeability-resistant and freeze-resistant alkali-activated geopolymer cementitious material, comprising the following substances: 22kg modified marine mud, 45kg slag, 8kg metakaolin, 20kg skeleton filler material, 2kg composite alkali activator; First, take modified marine mud, metakaolin and slag, mix and stir, then add skeleton filler material 2 and stir and mix, and collect the mixture; After taking the mixture and introducing carbon dioxide gas with the following parameters: pressure 0.08 MPa, rate 65 mL / min, and time 22 min, a composite alkali activator is added. After stirring and mixing, the mixture is vibrated and shaped. It is then steam-cured at 32℃ for 3 h, then at 52℃ for 5 h, and finally at 72℃ for 3 h, followed by natural curing for 14 days to obtain an impermeable and freeze-resistant alkali-activated geopolymer cementitious material.
[0038] Example 8 A permeability-resistant and freeze-resistant alkali-activated geopolymer cementitious material, comprising the following substances: 22kg modified marine mud, 45kg slag, 8kg metakaolin, 25kg skeleton filler material, 2kg composite alkali activator; First, take modified marine mud, metakaolin and slag, mix and stir, then add skeleton filler material 3 and stir and mix, and collect the mixture; After taking the mixture and introducing carbon dioxide gas with the following parameters: pressure 0.08 MPa, rate 65 mL / min, and time 22 min, a composite alkali activator is added. After stirring and mixing, the mixture is vibrated and shaped. It is then steam-cured at 32℃ for 3 h, then at 52℃ for 5 h, and finally at 72℃ for 3 h, followed by natural curing for 14 days to obtain an impermeable and freeze-resistant alkali-activated geopolymer cementitious material.
[0039] Comparative Example 1 Compared with Example 1, Comparative Example 1 used unmodified marine mud for treatment, and the remaining preparation steps and methods were the same as those in Example 1.
[0040] Performance testing Performance tests were conducted on Examples 1-8 and Comparative Example 1. Testing standard: Impermeability: GB / T 50082-2009 "Standard for Test Methods of Long-Term Performance and Durability of Ordinary Concrete"; Freeze-thaw resistance: GB / T 50082-2009 "Standard for Test Methods of Long-Term Performance and Durability of Ordinary Concrete"; 28-day compressive strength: GB / T 17671-1999 "Test Method for Strength of Cement Mortar (ISO Method)" The results are shown in Table 1 below: Table 1 Performance Test Table
[0041] From the above Examples 1-8 and Comparative Example 1, and by comparing the test results in Table 1, it can be found that: Based on the test results of Examples 1-5 and compared with Example 1 and Comparative Example 1, this application's technical solution addresses the two core problems of "organic matter inhibiting reaction" and "low silicon activity" naturally occurring in marine mud, designing a two-step modification process of "calcination + organic acid activation." Calcination removes organic matter from the marine mud at high temperatures, preventing it from hindering the diffusion and bonding of active ions during subsequent alkali activation and preventing the formation of loose pores within the material. Crushing and sieving optimize the particle size distribution of the marine mud, increasing the specific surface area and providing more reaction sites for organic acid activation. Organic acids, through protonation, disrupt the crystal structure of silicates in the marine mud, dissolving some metal impurity ions, releasing silicon as active silicon ions, enhancing its ability to participate in polymerization reactions, and solving the reaction lag problem caused by insufficient silicon activity when directly using marine mud.
[0042] By comparing Examples 6-8 with Examples 1-5, this application further illustrates that the mass ratio of desulfurized gypsum to porous skeleton particles is determined based on the balance requirement of "porosity-strength" of the skeleton filling material. If the proportion of desulfurized gypsum is too high, it will overfill the skeleton pores, resulting in too low porosity; if the proportion of desulfurized gypsum is too low, the skeleton pores cannot be fully filled, resulting in a loose structure, easy penetration of moisture into the material interior, poor impermeability, and insufficient skeleton support capacity, affecting the overall strength of the material. By adjusting the ratio of the two, the skeleton can form a structure of "appropriate porosity + dense bonding", which retains the pore space to buffer freeze-thaw stress, and reduces the penetration path through desulfurized gypsum filling, thus meeting the dual requirements of impermeability and freeze-thaw resistance. This proportion design avoids performance defects in the skeleton caused by component imbalance, ensuring that the skeleton can not only play a structural support role, but also synergistically improve impermeability and freeze resistance. The proportion range has strong process adaptability and can accommodate the compositional fluctuations of different batches of raw materials, reducing the difficulty of quality control in the production process. At the same time, a reasonable proportion can reduce raw material waste and control production costs while ensuring performance, thus providing a guarantee for the stability and economy of industrial production.
[0043] The present invention has been described in detail above with reference to specific embodiments and exemplary examples; however, these descriptions should not be construed as limiting the present invention. Those skilled in the art will understand that various equivalent substitutions, modifications, or improvements can be made to the technical solutions and embodiments of the present invention without departing from the spirit and scope of the invention, and all such modifications and improvements fall within the scope of the present invention. The scope of protection of the present invention is defined by the appended claims.
[0044] All publications, patent applications, patents, and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings commonly understood by those skilled in the art. In case of conflict, the definitions in this specification shall prevail.
[0045] When this specification uses the prefixes “known to those skilled in the art,” “prior art,” or similar terms to derive materials, substances, methods, steps, apparatus, or components, the objects derived from such prefixes cover those commonly used in the art at the time of this application, but also include those that are not currently commonly used but will become generally recognized in the art as suitable for similar purposes.
[0046] In the context of this specification, except where expressly stated otherwise, any matters or issues not mentioned shall apply directly to those known in the art without any modification.
Claims
1. An anti-permeation and anti-freezing type alkali-activated geopolymer cementitious material, characterized in that, Comprise the following weight parts of the following substances: Modified sea mud 20-25 parts; Slag 40-50 parts; Metakaolin 5-10 parts; Composite alkali activator 2-3 parts; The modified sea mud is an activated modified sea mud particle.
2. The anti-permeation and anti-freezing alkali-activated geopolymer cementitious material according to claim 1, characterized in that, The activated modified sea mud particle comprises the following preparation steps: After calcination treatment of the sea mud, the cooled sea mud is broken and sieved, an organic acid is added, and after stirring with water, the mixture is filtered, dried to obtain modified sea mud.
3. The anti-permeation and anti-freezing type alkali-activated geopolymer cementitious material according to claim 1, characterized in that, Further comprising 15-25 parts by weight of a skeleton filling material, the skeleton filling material is made by the following technical scheme: First, mix fly ash and bentonite, heat and calcine, stand and cool to room temperature, break and collect to obtain porous skeleton particles; Mix the porous skeleton particles with desulfurization gypsum, heat and hydrothermal reaction, add sodium hydroxide solution, heat and pressurize, keep warm and pressure, stand and cool to room temperature, wash and dry to obtain the skeleton filling material.
4. The freeze-thaw resistant alkali-activated geopolymer cementitious material of claim 3, wherein, The mass ratio of the desulfurization gypsum to the porous skeleton particles in the porous skeleton particles is 1: (2.5-3.5).
5. A method of producing an anti-permeation anti-freezing type alkali-activated geopolymer cementitious material according to any one of claims 1-4, characterized in that, Comprise the following preparation steps: First, mix modified sea mud, metakaolin and slag, stir, then add the skeleton filling material, stir and mix, collect the mixture; Pass carbon dioxide gas into the mixture, then add the composite alkali activator, stir and mix, vibrate and shape, steam curing, then natural curing for 14 days to obtain the impermeable and freeze-resistant alkali-activated geopolymer cementing material.
6. The method for preparing an anti-permeation and anti-freezing alkali-activated geopolymer cementitious material according to claim 5, characterized in that, The parameters for passing carbon dioxide gas are: pressure 0.05-0.1 MPa, rate 50-80 mL / min, time 20-25 min.
7. The method for preparing an impermeable and freeze-resistant alkali-activated geopolymer cementitious material according to claim 5, characterized in that, The steam curing is a stepwise steam curing treatment, the following technical scheme is adopted: first, steam curing at 30-35℃ for 3h, then steam curing at 50-55℃ for 5h, finally steam curing at 70-75℃ for 3h.